Evaluasi Program CIPP: Studi Atas Program Tahfidz Qur’an Pagi di MTs Tahfidzul Qur’an Azhar Center Makassar - Syafi'i, Ahmad; Alallah, Almutawakkil (Balai Diklat Keagamaan Surabaya, 2024)
The Tahfiz Qur’an Morning Program aims to improve students' ability to memorize the Qur'an with proper fasahah and tajweed, root the values of the Qur'an, and present the Qur'an in every aspect of life. This type of research is a CIPP model program evaluation with a qualitative case study approach. The results of this study: (1) In terms of context evaluation, the Tahfiz Qur'an Morning program at MTs Tahfidzul Quran Azhar Center Makassar has enabled students to increase their memorization beyond the 3 juz required by the school. (2) From the perspective of input evaluation, the coaches in the Tahfiz Qur'an Morning program have met the criteria as coaches of the Tahfiz Qur'an Morning program. The facilities and infrastructure that support the program are good enough. (3) Process evaluation shows that the implementation of the morning Quran memorization program at MTs Tahfidzul Quran Azhar Center Makassar uses the talqin method. This method involves repetition of reading the verses to be memorized by children until they master them. However, some obstacles were encountered, especially the lack of ability of students to memorize the verses of the Qur'an, which has an impact on this process. (4) Judging from the product evaluation, the implementation of the morning Quran memorization program has a positive impact on students, teachers, and the community as a whole.